(untitled) (Damascus University Journal for the economic and Political sciences, 2026)
This study aimed to test the impact of banks in Syria applying social responsibility in enhancing market value according to Tobin’s Q model, by analyzing data on private banks listed on the Damascus Stock Exchange during the period 2011-2021. To achieve the objectives of the study, we relied on the quantitative approach, using data published in the final annual reports of the banks sampled in the study, and relying on the content analysis method to measure social responsibility through the CSRDISC disclosure index. Data on responsibility activities were collected using the point method for a list of (25) activities. Social responsibility is classified into two activities (community service activities and product development activities). The statistical program EViews10 was relied upon to analyze the data and conduct tests. The results showed that the percentage of banks that implemented these two activities was low during the years of the study, as it did not exceed 16%. Through testing the hypotheses, the study concluded that there is a positive impact of applying social responsibility on Syrian banks listed on the Damascus Stock Exchange in enhancing their market value according to this model. The study also showed that there is a positive impact of community service activities، while there is no significant impact of product development activities. On the market value of banks in the Syrian market according to this model.